Metalaxyl Sensitivity Status of Downy Mildew Populations in Western Cape Vineyards - Fourie, P.H. (South African Journal of Enology and Viticulture, 2017)
Grapevine downy mildew, caused by Plasmopara viticola, is a sporadic, but destructive disease of grapevines in South Africa. Despite extensive fungicide spray programmes, disease control during disease-conducive weather periods is often inadequate, and severe losses were experienced during recent epidemics. Poor disease control can be attributed to several factors, one of which may be reduced efficacy of fungicides due to resistance build-up in the pathogen populations. P. viticola isolates were sampled during the 1999/2000, 2000/2001 and 2001/2002 seasons from various vineyards in the Western Cape province of South Africa and screened for sensitivity to metalaxyl using the floating leaf-disc method recommended by the Fungicide Resistance Action Committee. Minimum inhibitory concentration (MIC) values for 813 isolates were determined. Only 5.8% of the isolates tested had MIC values of 10 μg/mL and lower. The majority of the isolates (94.2 % ) showed MIC values of 100 μg/mL or more. These isolates were designated resistant to highly resistant. With the exception of one vineyard in a remote area where phenylamides had not previously been used, very high resistance frequencies were observed, irrespective of whether the samples were taken early or late in the season. This observation, supported by the consistent high resistance frequencies recorded over time in individual vineyards, is indicative of the stability of metalaxyl resistance in grapevine downy mildew populations. In view of the widespread occurrence and stability of resistance against metalaxyl, the use of phenylamide formulations for the control of downy mildew in Western Cape vineyards should be reconsidered.